Food for (e) thought : strategies of the urban poor in Johannesburg in achieving food security : an investigation of how gender and the pursuit of informal livelihoods affect household food-provisioning strategies in Tembisa, Gauteng Province. - Lakhani, Ishtar (My University, 2014)
This research report serves to explore how women living in Tembisa, the second largest township in Johannesburg, South Africa, create and maintain highly flexible and mobile personal networks, to maximize their access to financial and social capital in order to improve individual and household resilience to food insecurity. What are the strategies that are adopted, created and manipulated in the daily lives of the food insecure in an attempt to attain a semblance of food security for themselves, their households and their communities?
Keywords: Food security--South Africa.; Food supply--South Africa.; Poor women--South Africa--Economic conditions.